What explains spatial variations of COVID-19 vaccine hesitancy?: a social-ecological-technological systems approach - Arun Pallathadka; Heejun Chang; Daikwon Han (Environmental Research: Health, 2022)
While COVID-19 vaccines have been available since December 2020 and efforts have been made to vaccinate the maximum population, a large number of people are continuing to be hesitant, prolonging the pandemic in the US. While most previous studies investigated social, economic, and demographic variables that are associated with COVID-19 vaccine hesitancy, we added ecological and technological variables to better understand the spatial variations of vaccine rates in the contiguous United States using spatial regression and geographically weighted regression (GWR) models. We aim to identify spatially varying social, ecological, and technological factors that are associated with COVID-19 vaccination rates, which can aid in identifying and strengthening the public health system and vaccination programs that can eventually facilitate and overcome vaccination hesitancy. We found six statistically significant predictors; two predictors, % Republican voters (r = 0.507, p < .001) and % Black population (r = −0.360, p < .001) were negatively correlated with the vaccination rates, whereas four remaining predictors, % Population with college degree (r = 0.229, p < 001), NRI Score (r = 0.131, p < .001), % Population with broadband access (r = 0.020, p < 001), and Health facilities per 10 000 population (r = 0.424, p < 001) were positively correlated with the vaccination rates at the county level. GWR results show spatially varying relationships between vaccination rate and explanatory variables, indicating the need for regional-specific public health policy. To achieve widespread vaccination, addressing social, ecological, and technological factors will be essential. We draw particular attention to the spatial variances even among positively and negatively associated factors. This research also calls for a reexamination of existing practices, including vaccination communication and other public health policies, local and national public health organizations, telecommunications agents, and mobilization of resources by the public and private sectors.